Encasement material for power storage device, method for manufacturing the same, and power storage device
Patent Information
- Application Number
- CN202280047308.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-07-09
- Filing Date
- 2022-06-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-06-22
AI Technical Summary
[0034]根据发明[1]的蓄电设备用外包装材料,由于在外侧层的表面设置有包含阴离子系表面活性剂的易滑层作为最外层,因此能够获得所期望的润滑性,并能够提高成型性。此外,易滑层以特定的存在量形成,因此能够抑制必要以上的过度的润滑性(脱模性),也能够充分地确保对粘合胶带等粘合剂的粘接性,还能够可靠地防止粘合胶带的剥离等不良情况。此外,与阳离子系、非离子系相比,本发明的阴离子系表面活性剂的分散性优异,因此能够在外侧层表面整个区域没有间隙地形成表面活性剂的被膜(易滑层),从这一点考虑,也能够确保良好的润滑性并且获得充分的粘合性。
Smart Images

Figure CN117597819B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to outer packaging materials for energy storage devices such as lithium secondary batteries (lithium-ion batteries, lithium polymer batteries, etc.), lithium-ion capacitors, and double-layer capacitors, as well as their manufacturing methods and energy storage devices incorporating all-solid-state batteries. Background Technology
[0002] In recent years, with the trend towards thinner and lighter mobile electrical devices such as smartphones and tablets, the outer packaging materials for energy storage devices such as lithium-ion secondary batteries, lithium polymer secondary batteries, lithium-ion capacitors, and double-layer capacitors mounted on these devices have replaced traditional metal cans. These materials consist of laminates comprising a heat-resistant resin layer (heat-resistant layer), an adhesive layer, a metal foil layer (barrier layer), an adhesive layer, and a thermoplastic resin layer (thermoplastic bonding layer) (Patent Documents 1-3). Furthermore, there is an increasing trend of using these laminates (outer packaging materials) for packaging power supplies for electric vehicles, large power supplies for energy storage, and capacitors. When forming the outer packaging material for energy storage devices, the aforementioned laminate is embossed and deep-drawn to form a three-dimensional shape, such as a roughly rectangular parallelepiped. This three-dimensional shape ensures sufficient storage space for housing the main body of the energy storage device.
[0003] In order to perform deep drawing of the outer packaging material, it is preferable to reduce the friction between the outer layer surface (heat-resistant layer surface) and the inner layer surface (thermal fusion layer surface) and improve lubricity.
[0004] For example, conventionally, a lubricant such as a fatty acid amide is pre-added to the film constituting the heat-welding layer (heat-welding layer film), allowing the lubricant to seep out and thus achieving lubricity on the inner layer surface. Furthermore, the lubricity of the outer layer surface is achieved by transferring the lubricant from the heat-welding layer to the outer layer surface during an aging process while the outer packaging material is wound up.
[0005] On the other hand, in the past, in order to obtain lubricity on the outer surface of the outer layer of the outer packaging material, methods such as directly coating with lubricants such as fatty acid amides, easy-slip resins, and layering easy-slip resin layers were also used.
[0006] Existing technical documents
[0007] Patent documents
[0008] Patent Document 1: Japanese Patent No. 4736188
[0009] Patent Document 2: Japanese Patent No. 4940496
[0010] Patent Document 3: Japanese Patent Application Publication No. 2020-91990 Summary of the Invention
[0011] The problem that the invention aims to solve
[0012] However, for the method of adding lubricants such as fatty acid amides to the inner layer (thermal fusion layer), the amount of lubricant transferred to the outer layer is affected by temperature and pressure, so it is difficult to obtain uniform lubricity over the entire area of the outer layer surface, and there is a problem of difficulty in obtaining stable and good formability.
[0013] In addition, for methods such as applying lubricant to the outer layer surface, sometimes the total amount of lubricant applied to the outer layer and added to the inner layer becomes too large, resulting in problems such as inaccurate control of the amount of lubricant and difficulty in obtaining good moldability.
[0014] Furthermore, for the method of laminating slippery resin layers, the adhesive resin constituting the slippery resin layer requires various properties such as heat resistance, solvent resistance, wettability, and printability. Therefore, it is currently difficult to select a resin that meets all these properties.
[0015] On the other hand, the use of surfactants to impart lubricity in the outer packaging material was also considered. However, because surfactants have release properties, problems arise regarding adhesion. That is, most battery storage devices packaged in outer packaging materials are housed together with other electronic circuits within the casing. In this case, protective tape, mounting tape, or other adhesive tapes are applied to the outer surface of the battery packaging material for fixation, preventing the battery storage device from contacting other electronic circuits. Therefore, if only surfactants are used to impart lubricity, the problem arises where the tape cannot adequately adhere to the outer surface of the packaging material (the adhesive tape is easily peeled off).
[0016] The preferred embodiments of the present invention are made in view of the above-mentioned and / or other problems in related technologies. The preferred embodiments of the present invention can significantly improve upon existing methods and / or apparatuses.
[0017] The present invention was made in view of the above-mentioned problems, and aims to provide an outer packaging material for a storage device that can improve moldability and also ensure sufficient adhesion to adhesives such as tapes, as well as a method for manufacturing the same and the storage device.
[0018] Other objects and advantages of the present invention will become apparent from the following preferred embodiments.
[0019] Methods for solving problems
[0020] To address the aforementioned issues, the present invention provides the following means.
[0021] [1] An outer packaging material for an energy storage device, characterized in that the outer packaging material for the energy storage device comprises a barrier layer made of metal foil, a heat-resistant layer made of heat-resistant resin disposed on the outer surface side of the barrier layer, and a heat-fusion layer made of heat-fusion resin disposed on the inner surface side of the aforementioned barrier layer.
[0022] An easy-slip layer containing anionic surfactant is provided on the outer surface of the aforementioned heat-resistant layer.
[0023] The aforementioned slippery layer was set at a concentration of 1.0 mg / m³. 2 ~10.0mg / m 2 .
[0024] [2] The outer packaging material for the storage device as described in item 1 above, wherein the coefficient of dynamic friction of the outer surface of the aforementioned slippery layer based on JISK7125 (1999) is set to 0.05 to 0.3.
[0025] [3] The outer packaging material for the storage device as described in item 1 or 2 above, wherein the heat-fusion layer is composed of polypropylene resin containing a lubricant.
[0026] [4] The outer packaging material for the storage device as described in any one of the preceding items 1 to 3, wherein the aforementioned heat-resistant layer is composed of a multilayer structure comprising a first layer made of polyamide resin and a second layer made of polyester resin disposed on the outer surface side of the first layer.
[0027] [5] A method for manufacturing outer packaging material for energy storage devices, characterized in that the outer packaging material for energy storage devices comprises a barrier layer made of metal foil, a heat-resistant layer made of heat-resistant resin disposed on the outer surface side of the barrier layer, and a heat-fusion layer made of heat-fusion resin disposed on the inner surface side of the aforementioned barrier layer.
[0028] The manufacturing method includes coating the outer surface of the aforementioned heat-resistant layer with an anionic surfactant to form a coating amount of 1.0 mg / m². 2 ~10.0mg / m 2 The process of creating the slippery layer.
[0029] [6] An energy storage device, characterized in that the energy storage device comprises:
[0030] The main body of the energy storage device; and
[0031] The outer packaging material according to any one of claims 1 to 4,
[0032] The main body of the aforementioned energy storage device is wrapped in the aforementioned outer packaging material.
[0033] The effects of the invention
[0034] According to the outer packaging material for storage devices of the invention [1], since an easy-slip layer containing an anionic surfactant is provided on the surface of the outermost layer as the outermost layer, the desired lubricity can be obtained and the moldability can be improved. In addition, the easy-slip layer is formed in a specific amount, so excessive lubricity (release properties) beyond what is necessary can be suppressed, and the adhesion to adhesives such as adhesive tapes can be sufficiently ensured, and adverse conditions such as peeling of adhesive tapes can be reliably prevented. Furthermore, compared with cationic and nonionic surfactants, the anionic surfactant of the present invention has excellent dispersibility, so a surfactant film (easy-slip layer) can be formed without gaps in the entire area of the outermost layer surface. From this point of view, good lubricity and sufficient adhesion can also be ensured.
[0035] The outer packaging material for the storage device according to the invention [2] can achieve the above-mentioned effects more reliably because the coefficient of dynamic friction of the slippery layer surface is specified.
[0036] According to the invention [3], the outer packaging material for the storage device contains a lubricant in the heat-fusion layer that serves as the inner layer. The lubricant is then transferred to the slip layer, and the lubricating effect of the lubricant is combined with the lubricating effect brought about by the surfactant of the slip layer, so that the desired lubricity can be reliably imparted to the outermost surface.
[0037] According to the invention [4], the outer packaging material for the storage device is composed of a multilayer structure including an inner polyamide resin layer and an outer polyester resin layer. Therefore, the anionic surfactant, which is a slip layer, is easily dispersed on the surface of the outer polyester resin layer, and a slip layer can be reliably formed in the entire area of the outer layer surface. In addition, since a polyamide resin layer with excellent formability is disposed on the inner side, the formability is also excellent.
[0038] According to the manufacturing method of the outer packaging material for the storage device of the invention [5], an anionic surfactant is coated on the outer surface to form a slip layer, so the amount of slip layer coating and the film thickness can be freely controlled, and the desired lubricity can be given more reliably.
[0039] According to the invention [6], the outer packaging material of the above invention [1] has excellent formability and sealing properties, and therefore can provide a high-quality energy storage device with high operational reliability. Attached Figure Description
[0040] [ Figure 1 ] Figure 1 A cross-sectional view is shown for an outer packaging material for an energy storage device, which is an embodiment of the present invention.
[0041] [ Figure 2 ] Figure 2Figure (a) is a cross-sectional view and Figure (b) is a top view, illustrating the coating state of the surfactant in the outer packaging material for the energy storage device according to the embodiment.
[0042] [ Figure 3 ] Figure 3 A cross-sectional view is shown for an energy storage device made using the outer packaging material of the embodiment.
[0043] [ Figure 4 ] Figure 4 A perspective view showing the disassembled energy storage device of the embodiment. Detailed Implementation
[0044] Figure 1 This is a cross-sectional view showing the outer packaging material for an energy storage device according to an embodiment of the present invention. As shown in the figure, the outer packaging material 1 for the energy storage device includes a heat-resistant layer 2 made of heat-resistant resin as an outer layer, a heat-fusion layer (sealant layer) made of heat-fusion resin as an inner layer, and a barrier layer 4 as a metal foil layer (intermediate layer) disposed between the two layers 2 and 3, and an outermost slip-resistant layer 5 is formed on the outer surface of the heat-resistant layer 2.
[0045] The barrier layer 4 can be made of metal foil including aluminum (Al) foil, copper (Cu) foil, stainless steel (SUS) foil, nickel (Ni) foil, and titanium (Ti) foil, and is particularly preferably made of 1000 series and 8000 series Al foil as specified in JIS H4160. It should be noted that in this embodiment, the terms aluminum, copper, nickel, and titanium are used to mean that their alloys are also included.
[0046] The thickness of the barrier layer 4 is preferably set to 20μm to 100μm, and more preferably to 30μm to 80μm.
[0047] Furthermore, regarding the barrier layer 4, it is preferable to pre-treat at least the inner surface (the surface on the side of the heat-fusion layer 3) with a chemical conversion treatment. By performing this chemical conversion treatment, corrosion of the barrier layer surface by the contents (such as the battery electrolyte) can be effectively prevented.
[0048] The heat-resistant layer 2 can preferably be made of heat-resistant resins, such as biaxially oriented nylon film (ONy), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polyethylene 2,5-furandicarboxylate (PEF), biaxially oriented polypropylene (OPP), etc.
[0049] Furthermore, it is preferable to use a thermoplastic resin with a temperature 10°C or higher than that of the thermoplastic resin constituting the heat-fusion layer 3 as the heat-resistant resin, and more preferably a thermoplastic resin with a temperature 20°C or higher.
[0050] The heat-resistant layer 2 can be formed, for example, by bonding a resin film constituting the heat-resistant layer 2 to one side (outer surface) of the barrier layer (metal foil) 5 with an adhesive. The heat-resistant layer 2 can be composed of a single layer or a multi-layer structure, such as a structure obtained by stacking two or more resin films.
[0051] When the heat-resistant layer 2 is composed of a single layer, a polyester resin film such as PET is preferred. Furthermore, in the case of a single-layer structure, since the anionic surfactant is water-based, a film with low water absorption, such as polyethylene terephthalate (PET) film, can achieve its effect with a smaller amount compared to a film with high water absorption, such as biaxially stretched nylon (ONy) film. That is, in the case of ONy film, since the water is absorbed into the film, there is a concern that the coefficient of dynamic friction may increase with the same coating amount as PET film.
[0052] In addition, in the case of a two-layer structure, it is preferable to use a composite film obtained by combining a polyester film with a polyamide film such as nylon. Furthermore, in the case of a two-layer structure, it is preferable to use a structure in which a polyamide film is laminated on the outer surface of the barrier layer 4 and a polyester film is laminated on the upper surface (outer surface) of the polyamide film, that is, a structure in which the polyester is disposed on the outside of the polyamide.
[0053] The thickness of the heat-resistant layer 2 can be a single-layer structure or a multi-layer structure, preferably set to 10μm to 50μm.
[0054] Furthermore, as the adhesive used to bond the resin film for the heat-resistant layer 2 to the barrier layer 4, urethane-based adhesives, epoxy-based adhesives, and acrylic-based adhesives are preferably used. In addition, the thickness of this adhesive is preferably set to 1 μm to 5 μm.
[0055] The heat-fusion layer 3 may preferably be made of heat-fusion resins (thermoplastic resins) such as unstretched polypropylene (CPP) or polyethylene, with CPP being particularly preferred.
[0056] The heat-fusion bonding layer 3 can be formed, for example, by bonding a resin film constituting the heat-fusion bonding layer 3 to the other side (inner surface) of the barrier layer 4 using an adhesive. The heat-fusion bonding layer 3 can be composed of a single layer or a multi-layer structure. The thickness of the heat-fusion bonding layer 3 is preferably set to 20 μm to 100 μm.
[0057] In addition, in this embodiment, the resin constituting the heat-fusion layer 3 contains 100ppm to 2000ppm of lubricant.
[0058] As a lubricant, fatty acid amides such as saturated fatty acid amides and unsaturated fatty acid amides, as well as fatty acid diamides such as saturated fatty acid diamides, unsaturated fatty acid diamides, and aromatic diamides are preferred.
[0059] Specifically, examples of saturated fatty acid amides include lauryl amide, palmitamide, stearamide, benzyl amide, and hydroxystearamide.
[0060] Examples of unsaturated fatty acid amides include oleamide and erucamide.
[0061] Examples of the above-mentioned saturated fatty acid diamides include methylene bis-stearamide, ethylene bis-decanoic acid amide, ethylene bis-lauric acid amide, ethylene bis-stearamide, ethylene bis-hydroxystearamide, ethylene bis-sorbic acid amide, hexamethylene bis-stearamide, hexamethylene bis-sorbic acid amide, hexamethylene hydroxystearamide, N,N'-distearate adipamide, and N,N'-distearate sebacate amide.
[0062] Examples of the above-mentioned unsaturated fatty acid diamides include ethylene dioleamide, ethylene dierucamide, hexamethylene dioleamide, N,N'-dioleoyl adipamide, and N,N'-dioleoyl sebacate amide.
[0063] Examples of the aforementioned aromatic diamides include isophthalic dimethyl distearate, isophthalic dimethyl bishydroxy stearamide, and N,N'-distearate isophthalamide.
[0064] In addition, when the resin film for the heat-fusion bonding layer 3 is bonded to the barrier layer 4, dry lamination based on olefin-based adhesives, epoxy-based adhesives, especially acid-modified olefin-based adhesives, or hot lamination based on olefin-based or acid-modified olefin-based thermoplastic resins can be used.
[0065] In the case of dry lamination, the thickness of the adhesive should be set to 1μm to 5μm. In the case of hot lamination, the thickness of the thermoplastic resin used as the adhesive should be set to 5μm to 10μm.
[0066] In this embodiment, the slip-resistant layer (outermost layer) 5 is composed of anionic surfactants.
[0067] As anionic surfactants, preferred materials include carboxylates (soaps), sulfates, phosphates, palmitates, metal oleate salts, alkylnaphthalene sulfonates, sulfates of butyl oleate, octyl sulfate, hexadecyl sulfate, lauryl sulfate, and other organic sulfates with 8-18 carbon atoms; stearates, octyl sulfonates, hexadecyl sulfonates, lauryl sulfonates, stearyl sulfonates, oleyl sulfonates, p-toluene sulfonates, dodecylbenzene sulfonates, oleylbenzene sulfonates, naphthyl sulfonates, and diisopropylnaphthalene sulfonates, and other organic sulfonates with 8-30 carbon atoms. It should be noted that "salt" refers to a metal salt.
[0068] In this embodiment, as a specific example of anionic surfactant, the trade name "Elecut XC301-A" manufactured by Takemoto Oils & Fats Co., Ltd. can be used.
[0069] When forming the slip-resistant layer 5, a solution (slip-resistant layer solution) obtained by dissolving the above-mentioned anionic surfactant in a solvent such as water or alcohol is applied (coated) to the outer surface of the heat-resistant layer 2, and then dried to remove the solvent, thereby obtaining the product.
[0070] Here, because anionic surfactants exhibit excellent dispersibility in solvents such as water and alcohol, they are uniformly and without deviation distributed throughout the entire region of the aforementioned slippery solution. Therefore, as... Figure 2 As shown in (a) and (b), a slip-resistant layer 5, which is an anionic surfactant, can be formed seamlessly (without any uncoated areas) over the entire surface area of the heat-resistant layer 2 constituting the outer packaging material 1. For example, as... Figure 2 As shown in (a), even if there are uneven areas on the surface of the heat-resistant layer 2, the slip-resistant layer 5 is applied thinly to the uneven areas and thinly to the convex areas, thus ensuring that the slip-resistant layer 5 can be applied to the entire surface area regardless of the surface condition of the heat-resistant layer 2. It should be noted that... Figure 2 In (a), the uneven shape of the heat-resistant layer 2 is exaggerated for easy understanding of the invention.
[0071] Furthermore, unsaturated long-chain fatty acid salts such as anionic surfactants can be moderately dispersed and easily form surface protrusions (undulations), imparting good reactivity even with small amounts of coating. It should be noted that excessive coating can lead to overly strong release properties; therefore, to ensure a balance between release properties and reactivity, sodium oleate, especially anionic surfactants, is preferable.
[0072] In this embodiment, the coating amount (dry weight) of the slip-resistant layer 5 after solvent removal is preferably set to 1.0 mg / m³. 2 ~10.0mg / m 2 That is, if the coating amount is too small, the slip layer 5 cannot be formed without gaps on the entire outer surface of the heat-resistant layer 2, making it difficult to reliably obtain the desired lubricity and raising concerns about reduced moldability, which is not preferred. Conversely, if the coating amount is too large, there are concerns about significantly reduced release properties and decreased adhesion to the adhesive tape, which is also not preferred.
[0073] Regarding the outer packaging material 1 of this embodiment, while the heat-welded layer 3 side is the inner side and the slip-resistant layer 5 (heat-resistant layer 2) side is the outer side, it is subjected to a heat curing treatment in a rolled state. At this time, the lubricant contained in the heat-welded layer 3 is precipitated from the surface (inner surface side) of the heat-welded layer 3 and transferred to the slip-resistant layer 5 (heat-resistant layer 2) side, which is the outermost layer, thus imparting appropriate lubrication to the slip-resistant layer 5 and the heat-resistant layer 2. Therefore, the transferred lubricant combines with the lubricity of the slip-resistant layer 5 itself, and the desired lubricity can be obtained on the outer surface of the outer packaging material 1.
[0074] It should be noted that in this embodiment, the anionic surfactant used as the slip layer 5 contains only the transferred lubricant; other components, such as the solvent used when applying the slip layer solution, may remain. It should also be noted that the slip layer 5 does not contain particles such as anti-sticking materials (AB materials).
[0075] The outer packaging material 1 for the energy storage device of this embodiment, constructed in the manner described above, is used as the outer packaging shell of the energy storage device by directly forming it in sheet form or by thermoforming as needed through deep drawing, bulging, or other thermoforming processes.
[0076] For example, Figure 3 and Figure 4 The figures show a cross-sectional view and an exploded perspective view of the energy storage device 30 manufactured using the outer packaging material 1 of this embodiment. As shown in both figures, the energy storage device 30 is a lithium-ion secondary battery. In this embodiment, the outer packaging shell 15 is composed of a tray component 14 formed by molding the outer packaging material 1 and a cover component 10 made of the planar (sheet-like) outer packaging material 1. The energy storage device 30 is then constructed as follows: a generally cuboid-shaped main body of the energy storage device (electrochemical element, etc.) 31 is housed in the receiving recess of the tray component 14 formed by molding the outer packaging material 1 of the present invention; the cover component 10 (outer packaging material 1) of the present invention is arranged on the inner (lower) side of its heat-welded layer 3 on the main body of the energy storage device 31; the outer peripheral edge of the heat-welded layer 3 of the cover component 10 and the heat-welded layer 3 of the flange portion (sealing peripheral portion) 29 of the tray component 14 are sealed together by heat sealing. It should be noted that the inner surface of the receiving recess of the tray component 14 becomes the heat-welding layer 3, and the outer surface of the receiving recess becomes the slip-resistant layer 5 (heat-resistant layer 2) side (see...). Figure 4 ).
[0077] Figure 3In the attached drawing, reference numeral "39" refers to the heat-sealed portion formed by joining (welding) the outer periphery of the cover component 10 with the flange portion (sealing periphery) 29 of the tray component 14. It should be noted that in the energy storage device 30, the front end of the connecting wire (tab lead) connected to the main body 31 of the energy storage device is led out to the outside of the outer packaging shell 15, and is not shown in the figure.
[0078] The main body 31 of the energy storage device is not particularly limited; for example, a battery main body, a capacitor main body, or a capacitor body can be cited.
[0079] It should be noted that in the above embodiments, the outer packaging shell 15 is composed of a tray component 14 obtained by molding the outer packaging material 1 and a planar cover component 10. However, the present invention is not particularly limited to such a combination. For example, the outer packaging shell 15 may be composed of a pair of planar (sheet-like) outer packaging materials 1, or it may be composed of a pair of tray components 14 overlapping in an opposing state.
[0080] As described above, the outer packaging material 1 according to this embodiment obtains sufficient lubricity due to the formation of the slip layer 5 on the outer surface, and the heat-fusion layer 3, which is the inner layer, obtains sufficient lubricity due to the lubricant, thus reliably improving its formability.
[0081] In particular, since the slip layer 5 is provided without gaps across the entire outer surface of the outer packaging material 1, the desired lubricity can be reliably obtained, and the moldability can be improved more reliably. Here, in this embodiment, the coefficient of kinetic friction of the outer surface of the slip layer 5 is set to 0.05 to 0.3. Therefore, as mentioned above, good lubricity can be obtained, and sufficient moldability can be reliably obtained.
[0082] It should be noted that in this embodiment, the coefficient of kinetic friction is measured according to JIS K7125 (1999).
[0083] In addition, the coating amount of the slip-resistant layer 5 is set to 1.0 mg / m². 2 ~10.0mg / m 2 The slip layer is thin and uniformly formed over the entire outer surface, thus suppressing excessive lubricity and excessive release. Therefore, the outer surface of the outer packaging material 1 (slip layer 5) can adequately ensure the adhesion of the adhesive tape and reliably prevent defects such as tape peeling. Furthermore, since the slip layer 5 has a coefficient of dynamic friction of 0.05 or higher, the adhesion of the adhesive tape can be more reliably ensured from this perspective.
[0084] In addition, in this embodiment, an easy-slip layer 5 is formed by coating the outer surface of the heat-resistant layer 2 with an easy-slip layer solution. Therefore, compared with the case where an easy-slip layer is formed by transfer from the heat-welding layer 3 or by dissolution from the heat-resistant layer 2, the coating amount and film thickness of the easy-slip layer 5 can be freely controlled, the desired lubricity can be reliably imparted, and the quality and reliability of the outer packaging material 1 can be further improved.
[0085] In addition, in this embodiment, when the heat-resistant layer 2 is composed of two layers, an inner polyamide resin layer (first layer) and an outer polyester resin layer (second layer), it is assumed that the outer polyester resin layer is prone to being charged on the negative side. Therefore, it can be inferred that the anionic surfactant is easy to disperse on its surface (not easy to aggregate), and a film (easy-slip layer 5) based on the anionic surfactant can be uniformly formed throughout the entire outer surface area, and the desired lubricity can be reliably imparted.
[0086] Examples [Table 1]
[0087]
[0088] <Example 1>
[0089] As a barrier layer 4, a chemical conversion treatment solution containing phosphoric acid, polyacrylic acid (acrylic resin), chromium (III) salt compound, water, and alcohol is coated on both sides 5 of a 40 μm thick aluminum foil (A8021-O), and then dried at 180°C to form a chemical conversion coating. The chromium deposition of this chemical conversion coating is 10 mg / m² on each side. 2 .
[0090] Next, as shown in Table 1, a heat-resistant layer 2 is formed on one side (outer surface) of the aluminum foil (barrier layer 4) after the aforementioned chemical conversion treatment, in a two-layer structure. Specifically, a 15 μm thick biaxially stretched nylon 6 (ONy) film is dry-laminated onto one side (outer surface) of the aluminum foil (barrier layer 4) using a two-component curable urethane adhesive (3 μm thick) to form the first layer of the heat-resistant layer 2. Then, a 12 μm thick stretched polyethylene terephthalate (PET) film is dry-laminated onto the upper surface (outer surface) of the biaxially stretched nylon 6 (ONy) film using a two-component curable urethane adhesive (3 μm thick) to form the second layer of the heat-resistant layer 2. Thus, a substrate film with the heat-resistant layer 2 laminated on the upper surface (outer surface) of the barrier layer 4 is formed.
[0091] Next, a solution (solution for the slip layer) containing sodium oleate (referred to as "anionic surfactant A" in Table 1) as an anionic surfactant is applied to the surface of the outer layer (heat-resistant layer 2) of the substrate film. The solution is then dried at 150°C to form the slip layer 5 on the heat-resistant layer 2. The coating amount of the dried slip layer 5 is 2.5 mg / m², as shown in Table 1. 2 .
[0092] Next, using a two-component curable maleic acid-modified polypropylene adhesive (2 μm thick), a 40 μm thick unstretched polypropylene (CPP) film is laminated onto the other side (inner surface) of the aluminum foil (barrier layer 4) of the aforementioned substrate film. This is sandwiched between a rubber roller and a laminating roller heated to 100°C, and then pressed together to perform dry lamination, resulting in a laminate for the outer packaging material. This laminate is then wound onto a roller and cured at 40°C for 10 days to obtain a sample of the outer packaging material 1 of Example 1.
[0093] It should be noted that, regarding the method for determining the coating amount of the slip-resistant layer 5 shown in Table 1, the outer packaging material 1 is prepared to be cut into test pieces of 10cm × 10cm, and the weight of the test pieces is determined using a precision balance (minimum value 1μg). The weight at this time (weight before wiping) is set as "W0" mg.
[0094] Next, wipe the surface of the heat-resistant layer of the test piece with a cotton ball soaked in ethanol. After the test piece is fully dried, measure its weight using a precision balance. Set this weight (weight after wiping) as "W1" mg. Then, calculate the coating amount using the formula "(W1-WO)×100=coating amount".
[0095] <Examples 2-4>
[0096] As shown in Table 1, the coating amount of the slip-resistant layer 5 is set to "1 mg / m". 2 "6.5mg / m" 2 "10mg / m" 2 In addition, the same procedure as in Example 1 was followed to obtain samples of outer packaging material 1 for Examples 2 to 4.
[0097] <Example 5>
[0098] As shown in Table 1, sodium sulfate (referred to as "anionic surfactant B" in Table 1) was used as the anionic surfactant. Otherwise, the procedure was the same as in Example 1 to obtain the sample of outer packaging material 1 of Example 5.
[0099] <Example 6>
[0100] As shown in Table 1, the heat-resistant layer 2 is composed of a single layer of biaxially stretched nylon 6 (ONy) film with a thickness of 25 μm. Otherwise, the same procedure as in Example 1 is followed to obtain a sample of the outer packaging material 1 of Example 6.
[0101] <Example 7>
[0102] As shown in Table 1, the heat-resistant layer 2 is composed of a single layer of stretched polyethylene terephthalate (PET) film with a thickness of 12 μm. Otherwise, the same procedure as in Example 1 is followed to obtain a sample of the outer packaging material 1 of Example 7.
[0103] <Example 8>
[0104] As shown in Table 1, using anionic surfactant B for slip-resistant layer 5, the coating amount of slip-resistant layer 5 was set to 1 mg / m³. 2 Otherwise, the same procedure was followed as in Example 1 to obtain a sample of the outer packaging material 1 of Example 8.
[0105] <Example 9>
[0106] As shown in Table 1, sodium stearyl sulfonate (referred to as "anionic surfactant C" in Table 1) was used as the anionic surfactant, and the coating amount of the slip layer 5 was set to "4.5 mg / m²". 2 In addition, the same procedure as in Example 1 was followed to obtain a sample of the outer packaging material 1 of Example 9.
[0107] <Comparative Example 1> [Table 2]
[0108]
[0109] As shown in Table 2, without the formation of the slippery layer 5, the same procedure as in Example 1 was followed to obtain the outer packaging material 1 of Comparative Example 1.
[0110] <Comparative Example 2>
[0111] As shown in Table 2, a cationic surfactant was used instead of anionic surfactants to form the outermost layer (equivalent to a slip layer). Otherwise, the procedure was the same as in Example 1 to obtain the outer packaging material 1 of Comparative Example 2.
[0112] <Comparative Example 3>
[0113] As shown in Table 2, a nonionic surfactant was used instead of anionic surfactants to form the outermost layer (equivalent to a slip layer). Otherwise, the procedure was the same as in Example 1 to obtain the outer packaging material 1 of Comparative Example 3.
[0114] <Comparative Example 4>
[0115] As shown in Table 2, for the amide-based lubricant (fatty acid amide), isopropanol (IPA) was used as a solvent for coating, and the IPA was dried at 150°C, thereby forming on the outer surface of the heat-resistant layer 2 to form the outermost layer (equivalent to the slip layer). Otherwise, the same procedure as in Example 1 was followed to obtain the sample of the outer packaging material 1 of Comparative Example 4.
[0116] <Comparative Examples 5 and 6>
[0117] As shown in Table 2, the coating amount of the slip-resistant layer 5 is set to "0.5 mg / m". 2 "12mg / m" 2 Otherwise, the same procedure was followed as in Example 1 to obtain samples of outer packaging material 1 for Comparative Examples 5 and 6.
[0118] <Coefficient of kinetic friction>
[0119] In each of the outer packaging materials of the examples and comparative examples, as described in the embodiments above, the coefficient of kinetic friction of the outermost surface (the surface of the heat-resistant layer in Comparative Example 1) was measured according to JIS K7125 (1999). The results are shown in Tables 1 and 2.
[0120] <Tape peel test>
[0121] Test pieces with a width of 15 mm and a length of 150 mm were cut from the outer packaging material 1 of the examples and comparative examples. Adhesive tape (trade name "tesa 70415") with an adhesive strength of 13 N / cm was pasted onto the surface of each test piece along its length. The adhesive tape was 5 mm wide and at least 80 mm long. A 2 kgf manual roller was then moved back and forth across the adhesive tape 5 times, and the pieces were then left to stand at room temperature for 1 hour.
[0122] Next, using a Shimadzu Strograph (AGS-5kNX) tensile testing machine, one chuck was used to hold and fix the end of the test piece, while the other chuck held the end of the adhesive tape. Then, the peel strength at a peel speed of 300 mm / min and a peel angle of 180° was measured according to JIS K6854-3 (1999). The stable value of this measurement was taken as the adhesion force between the outermost surface and the adhesive tape (unit: N / 5mm).
[0123] Furthermore, as an evaluation criterion for the adhesion between the outermost surface of the heat-resistant resin layer and the adhesive tape, cases with an adhesion force of 6 N / 5 mm or more were designated as "◎ (very high)", cases with an adhesion force of 5 N / 5 mm or more but less than 6 N / 5 mm were designated as "○ (high)", and cases with an adhesion force less than 5 N / 5 mm were designated as "× (low)". The results are shown in Tables 1 and 2.
[0124] <Tests on moldability>
[0125] 100mm × 100mm test pieces were cut from the outer packaging materials 1 of the examples and comparative examples. For each test piece, a deep drawing test was conducted by changing the forming height (drawing depth) in 0.5mm increments using a deep drawing die installed on a 25t press.
[0126] Furthermore, if the specified moldability is achieved when the molding height is 8 mm or more, the rating is "◎"; if the specified moldability cannot be achieved within the range of 6 mm or more but less than 8 mm, the rating is "○"; and if the specified moldability cannot be achieved when the molding height is less than 6 mm, the rating is "×". The results are shown in Tables 1 and 2.
[0127] <Appearance Test (White Powder Test)>
[0128] From each of the outer packaging materials 1 in the examples and comparative examples, 600 mm of packaging material (test piece) was cut out along the MD direction.
[0129] On the other hand, after wrapping kimbi paper around a 1.3kg stainless steel (SUS) weight with an area of 55mm×50mm, green waste (black) is wrapped around it to prepare the green waste with the weight.
[0130] Then, the aforementioned green waste material with added weights was placed on the outermost surface of the test piece and pulled at a length of 400 mm, a speed of 4 cm / s, and an angle horizontal to the bottom surface. It should be noted that the green waste material used was the TRUSCO SSD2525 3100 antistatic sheet.
[0131] The surface (contact surface) of the green waste material after contact with the outermost surface of the test piece using the above method was visually observed. Significant white powder production was rated as "×", moderate white powder production as "○", and no white powder or virtually none as "◎". The results are shown in Tables 1 and 2.
[0132] <Overall Review>
[0133] As shown in Table 1, the outer packaging materials 1 of Examples 1 to 9 related to the present invention received good evaluations in all aspects, including tape adhesion, formability, and white powder generation. In particular, the outer packaging materials 1 of Examples 1 to 7, in which the coefficient of kinetic friction was adjusted to the range of 0.05 to 0.3, received even better evaluations.
[0134] Furthermore, the formability of Example 1 is superior to that of Examples 6 and 7. This is because in Example 1, the heat-resistant layer is a multilayer structure of PET film and ONy film, while in Examples 6 and 7 it is a single-layer structure of ONy film and PET film, thus improving the formability of the substrate.
[0135] On the other hand, as shown in Table 2, all of the outer packaging materials in Comparative Examples 1 to 6, which are beyond the scope of this invention, received poor evaluations.
[0136] This application claims priority to Japanese Patent Application No. 2021-114008, filed on July 9, 2021, the disclosure of which forms a direct part of this application.
[0137] It must be understood that the terms and expressions used herein are for illustrative purposes only and are not intended to be limiting or restrictive, nor do they exclude any equivalents of the features shown and stated herein, nor do they preclude various modifications within the scope of the claims made herein.
[0138] Industrial availability
[0139] The outer packaging material for energy storage devices of the present invention can be appropriately used in the manufacture of energy storage devices such as batteries and capacitors used in portable devices such as smartphones and tablets, hybrid vehicles, electric vehicles, wind power generation, solar power generation, and nighttime electricity storage applications.
[0140] Explanation of reference numerals in the attached figures
[0141] 1: Outer packaging materials
[0142] 2: Heat-resistant layer
[0143] 3: Heat fusion layer
[0144] 4: Barrier layer
[0145] 5: Slippery layer
[0146] 10: Cover components (outer packaging materials)
[0147] 14: Pallet components (outer packaging materials)
[0148] 15: Outer packaging shell (outer packaging material)
[0149] 30: Energy storage equipment
[0150] 31: Main body of the equipment
Claims
1. Outer packaging material for energy storage equipment, characterized in that, The outer packaging material for the energy storage device comprises a barrier layer made of metal foil, a heat-resistant layer made of heat-resistant resin disposed on the outer surface of the barrier layer, and a heat-fusion layer made of heat-fusion resin disposed on the inner surface of the barrier layer. An easy-slip layer containing an anionic surfactant is provided on the outer surface of the heat-resistant layer. The amount of the slippery layer is set at 1.0 mg / m³. 2 ~10.0mg / m 2 .
2. The outer packaging material for energy storage devices as described in claim 1, wherein, The coefficient of dynamic friction of the outer surface of the slip-resistant layer, based on JIS K7125-1999, is set to 0.05~0.
3.
3. The outer packaging material for energy storage devices as described in claim 1 or 2, wherein, The heat-fusion layer is made of polypropylene resin containing lubricant.
4. The outer packaging material for energy storage devices as described in claim 1 or 2, wherein, The heat-resistant layer is composed of a multilayer structure comprising a first layer made of polyamide resin and a second layer made of polyester resin disposed on the outer surface of the first layer.
5. A method for manufacturing outer packaging material for energy storage equipment, characterized in that, The outer packaging material for the energy storage device comprises a barrier layer made of metal foil, a heat-resistant layer made of heat-resistant resin disposed on the outer surface of the barrier layer, and a heat-fusion layer made of heat-fusion resin disposed on the inner surface of the barrier layer. The manufacturing method includes forming a coating with a coating amount of 1.0 mg / m² by coating an anionic surfactant onto the outer surface of the heat-resistant layer. 2 ~10.0mg / m 2 The process of creating the slippery layer.
6. An energy storage device, characterized in that, The energy storage device includes: The main body of the energy storage device; and The outer packaging material according to any one of claims 1 to 4, The main body of the energy storage device is wrapped by the outer packaging material.
Citation Information
Patent Citations
JP1972036188U
JP1974040496A
Exterior material for power storage device and power storage device
JP2020091990A
Attendance management device and attendance management program
JP2021114008A
Laminated film for battery, and battery container using it
JP2002056823A